Political Illiberalism in the Philippines: Analyzing Illiberal Political Values - Borja, Anthony Lawrence A. (Animo Repository, 2023)
Politicians are empowered as representatives of varying visions of the public good. If inquiries are made on why disruptive actors can ascend to high positions of political and moral authority, then due focus must be given on their psychopolitical roots. Through quantitative analysis and by reverse engineering the concept of political illiberalism from recent normative theories of political liberalism, this study illustrates that political illiberalism in the Philippines is a political value system characterized by (1) support for liberal institutions qualified in favor of political leadership and (2) political intolerance. These tendencies form the psychopolitical base of disciplinarian and leader-centric tendencies that have been observed in recent studies. Moreover, in order to show that this is a sustained tendency, this study utilizes the fourth and fifth waves of the Asia Barometer Survey. Overall, many Filipinos want liberal institutions like the rule of law and representative politics to exist alongside strong leaders and political exclusion.